Factors influencing online insurance purchasing decision-making among car owners in Mafikeng - Ndeudjeu, Joseline Nadia; Potgieter, M (Edelweiss Applied Science and Technology, 2025)
This study explores the factors influencing online car insurance purchasing decisions among car owners in Mafikeng, in the context of rising digital adoption in the insurance sector. The extended Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) were applied to investigate determinants such as trust, service quality, consumer attitudes, and social media influence. The research used a quantitative approach with a cross-sectional design conducted among 200 car owners. Data were collected using a structured questionnaire and analyzed with Chi-square tests, with reliability and validity confirmed. The results show that trust, service quality, consumer attitudes, and social media promotion significantly influence online purchasing decisions, while social media usage and perceived tangibility have relatively weaker effects. The findings highlight the importance of enhancing trust, transparency, and service quality in online insurance platforms. Insurance providers should also leverage targeted and credible social media strategies to foster consumer engagement and adoption in Mafikeng’s digital insurance market. By integrating TAM and TPB, this study contributes to the limited literature on digital insurance adoption in emerging markets and provides actionable insights for insurers seeking to strengthen customer trust and participation in online platforms.